Group-Based Online Job Interview Training Program Using Virtual Robot for Individuals With Autism Spectrum Disorders - Kumazaki, Hirokazu; Yoshikawa, Yuichiro; Muramatsu, Taro; Haraguchi, Hideyuki; Fujisato, Hiroko; Sakai, Kazuki; Matsumoto, Yoshio; Ishiguro, Hiroshi; Sumiyoshi, Tomiki; Mimura, Masaru (Frontiers in Psychiatry, 2022)
The rapid expansion of online job interviews during the COVID-19 pandemic is expected to continue after the pandemic has subsided. These interviews are a significant barrier for individuals with autism spectrum disorders (ASD). There is little evidence-based training for online job interviews for individuals with ASD, and the development of new trainings is expected. In an effort to facilitate online job interview skill acquisition for individuals with ASD, we developed a group-based online job interview training program using a virtual robot (GOT). In GOT, the interviewer and interviewee are projected as virtual robots on the screen. Five participants were grouped and performed the role of interviewee, interviewer, and evaluator. The participants perform all roles in a random order. Each session consisted of a first job interview session, feedback session, and second job interview session. The participants experienced twenty five sessions. Before and after GOT, the participants underwent a mock online job interview with a human professional interviewer (MOH) to evaluate the effect of GOT. In total, 15 individuals with ASD took part in the study. The GOT improved self-confidence, motivation, the understanding of others’ perspectives, verbal competence, nonverbal competence, and interview performance scores. There was also a significant increase in the recognition of the importance of the point of view of interviewers and evaluators after the second MOH compared to after the first MOH. Using a VR robot and learning the importance of interview skills by experiencing other perspectives (i.e., viewpoint of interviewer and evaluator) may have sustained their motivation and enabled greater self-confidence. Given the promising results of this study and to draw definitive conclusions regarding the efficacy of virtual reality robots for mock online job interview training, further studies with larger, more diverse samples of individuals with ASD using a longitudinal design are warranted.